Estudio De La Demanda Para La Implementación De Una Empresa De Acopio Y Comercialización De Productos Frescos A Domicilio, Riobamba-Ecuador - Arrieta, Marco Vivar; Altamirano, Juan Pablo Haro (European Scientific Journal, ESJ, 2018)
This paper focuses on studying the demand for the implementation of a company that deals with the processing and marketing of fresh products “home delivery” in Riobamba. Through a general diagnosis, it was determined that the demand considers that the acquisition of products is a waste of time. It could be devoted to other priorities or productive activities, such that they can be an alternative. The universe comprising of 24086 families was considered, being the economic level of medium to high and delimiting technical recommendations for the attention of 4% of the population. The potential clients, therefore, are 963 families. The sample was determined for 275 surveys and served to demonstrate the behavior of consumers. Based on secondary information and quantitative research, surveys were designed, applied, and systematized. As a result, 88% of people cook at home while 44% of mother takes charge of buying the products. The frequency of product acquisition is 44% weekly and 25% biweekly. 35% buy its products in the establishments of its preference due to good service, 30% acquires its products by variety, 91% express that they would pay for this service an additional 10% of the total cost of the basket. The purpose of this study was to verify the characteristics of the consumer and expose the alternative of acquiring quality fresh products and fair prices for Riobamba families. It also aims to offer at the same time the added worth of home delivery.